The influence of Corporate Social Responsibility (CSR) activities on consumers’ purchasing behavior - Teh, Boon Heng; Ong, Tze San; Pang, Lai Teng; Haslinah Muhammad; Ong, Tze Chin (Penerbit Universiti Kebangsaan Malaysia, 2019)
The purpose of this paper is to examine the influence of Corporate Social Responsibility (CSR) activities, which include economic, environmental, social, and legal concerns on consumers’ purchasing behavior in the Malaysian context. A questionnaire was developed to collect data from the respondents using snowballing sampling. This research found mixed results in term of significance of the relationships between economic, social, and legal concerns and consumers’ purchasing behavior. Environmental concerns had an insignificant relationship with consumers’ purchasing behavior. The results of this research may help managers in managing their businesses, since a single CSR strategy cannot be competitive for corporations to participate in the current global business environment. The findings may be useful to policymakers as it encourages corporations to engage actively in CSR. The outcome of this research may expand the knowledge base on CSR, since most of the investigations on consumers’ responses to CSR have been limited to a few states in Malaysia.